Pengaruh Kompetensi Karyawan Dan Beban Kerja Karyawan Terhadap Kinerja Karyawan Pada PT. Permodalan Nasional Madani Cabang Bogor - Ayu Rahmawati; Widhi Wicaksono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Business competition which is currently quite tight gives demands on companies and employees to be able to maintain their business, this can also have an impact on employee workload and the need for competent employees. The purpose of this study was to determine the partial and simultaneous effects of employee competence and employee workload on employee performance at PT Permodalan Nasional Madani Bogor branch. The research method used is descriptive with a quantitative approach with a population and sample of 65 respondents, data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this study indicate that employee competence (X1) and employee workload (X2) affect employee performance (Y).